Interferon-α reduces the gefitinib sensitivity of human non-small cell lung cancer - Pan, Chi; Weng, Shanshan; Duan, Yin; Ding, Ling; Zhang, Suzhan; Huang, Jianjin (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Many studies have shown that interferon-α(IFN-α) enhances the antiproliferative effect of gefitinib in some solid tumours. We aimed to determine the effect of combining IFN-αwith gefitinib in human non-small cell lung cancer (NSCLC) cell lines (A549, H1299, HCC827) with different EGFR and K-Ras gene statuses. Material and methods : An MTT assay was used to assess cell proliferation. Apoptosis was detected by an Annexin V/propidium iodide assay using flow cytometry, and western blotting was used to determine the expression of epidermal growth factor receptor/phosphorylated epidermal growth factor receptor (EGFR/p-EGFR) and signal transducers and activators of transcription 3/phosphorylated signal transducers and activators of transcription 3 (STAT3/p-STAT3). Results : There was an additive interaction when gefitinib was combined with IFN-α in all cell lines; however, there was antagonism when gefitinib followed IFN-α pretreatment in three cell lines. Notably, IFN-α pretreatment significantly reduced the gefitinib sensitivity of HCC827 cells. Surprisingly, while IFN-α inhibited STAT3 phosphorylation in cell lines, gefitinib could do so. Conclusions : The results might confirm the hypothesis that IFN-α induces gefitinib sensitivity of NSCLC, and IFN-α inhibits phosphorylation of STAT3, which may be dependent on EGFR signal activation playing a role in the reduction of gefitinib sensitivity after IFN-α treatment in NSCLC cell lines.